Resolving the cause of recurrent Plasmodium vivax malaria probabilistically - Aimee R. Taylor (Nature Portfolio, 2019)
Relapse, reinfection and recrudescence can all cause recurrent infection after treatment of Plasmodium vivax malaria in endemic areas, but are difficult to distinguish. Here the authors show that they can be differentiated probabilistically and thereby demonstrate the high efficacy of primaquine treatment in preventing relapse.